Identifikasi Hidrokuinon pada Krim Pemutih yang Beredar di Pasar Kecamatan Proppo Kota Pamekasan Madura menggunakan Kromatografi Lapis Tipis (KLT) - Rohmadhani, Oktaviana; Asworo, Riska Yudhistia; Wattiheluw, Muhammad Hasan (NUTRITURE JOURNAL, 2026)
Based on Press Release Number HM.01.1.2.08.25.137 dated August 1, 2025, issued by the Indonesian Food and Drug Authority (BPOM), a number of cosmetics containing prohibited active ingredients are still being found, with 34 products proven to contain hazardous substances such as hydroquinone. According to the Regulation of the Head of BPOM Number 17 of 2022 concerning the Amendment to BPOM Regulation Number 23 of 2019, the use of hydroquinone is not permitted for direct application to the skin, which necessitates further research to identify its presence in whitening creams. This study utilized the Thin Layer Chromatography method in reference to the Regulation of the Head of the Food and Drug Authority of the Republic of Indonesia Number HK.03.1.23.08.11.07.331 of 2011 concerning Methods of Cosmetic Analysis. The results showed that the Rf​ values for the seven samples—consisting of samples labeled with BPOM registration numbers (S2 and S6), labeled samples without registration numbers (S3, S4, and S5), and unlabeled samples (S1 and S7)—were 0.2 for S1, 0.25 for S2, 0.38 for S3, 0.21 for S4, 0.18 for S5, 0.19 for S6, and 0.20 for S7. These test results confirmed that 6 out of the 7 whitening creams tested, specifically samples S1, S2, S4, S5, S6 and S7, were positive for hydroquinone, demonstrating that many whitening creams containing this substance are still circulating in the Proppo District Market.